Potential safety issues and other factors that may affect the introduction and uptake of rotavirus vaccines. (1st December 2016) - Aliabadi, N.; Tate, J.E.; Parashar, U.D.
Abstract: Rotavirus vaccines have demonstrated significant impact in reducing the burden of morbidity and mortality from childhood diarrhoea in countries that have implemented routine vaccination to date. Despite this success, in many countries, rotavirus vaccine coverage remains lower than that of other routine childhood vaccines. Several issues may potentially affect vaccine uptake, namely safety concerns related to intussusception with consequent age restrictions on rotavirus vaccination, contamination with porcine circovirus, vaccine-derived reassortant strains and hospitalization in newborn nurseries at time of administration of live oral rotavirus vaccine. In addition to these safety concerns, other factors may also affect uptake, including lower vaccine efficacy in the developing world, potential emergence of strains escaping from vaccine protection resulting in lower overall impact of a vaccination programme and sustainable vaccine financing. Although further work is needed to address some of these concerns, global policy bodies have reaffirmed that the benefits of rotavirus vaccination outweigh the risks, and vaccine use is recommended globally.